Analysis of the Trade Cycle in the UK and its Relationship to the Business Cycle - Fitra Prasapawidya Purna; Ibrahim Sorie Kamara (Universitas Ahmad Dahlan, Yogyakarta, 2022)
This study aims to analyze the trade cycle in the UK and analyze its relationship to the business cycle. This study uses secondary quarter data in the form of exports, imports, and UK GDP from 1987 to 2016. Band-pass filter data filter method is used in this study to isolate short-term cycles and assume an average growth of each variable. The results of this study indicate that the trade cycle in the UK has a medium-term cycle of around 2-4 years for both exports and imports. And there is a significant relationship between global economic events and movements in the trade cycle. Like in the early 2000s and late 2008. The relationship that exists in the cycle, especially the trade cycle between exports and imports, is found to be procyclical where the conditions are mutually exclusive. Meanwhile, between the trade cycle and the business cycle in the UK, there are many counter-cyclical situations where the relationship between the two cycles is inversely proportional. This is different from the findings of previous studies.